Self-adhesive resin cements: adhesive performance to indirect restorative ceramics - Zorzin, José Ignacio; Belli, Renan; Wagner, Anna; Petschelt, Anselm; Lohbauer, Ulrich (Journal of Adhesive Dentistry, 2014)
To evaluate the bonding performance of self-adhesive resin cements to zirconia and lithium disilicate in self- and dual-curing modes before and after thermocycling.Rectangular bars (3 mm high, 3 mm wide, 9 mm long) were manufactured from zirconia (Vita In-Ceram YZ for inLab, VITA) and lithium disilicate blocks (IPS e.max Press, Ivoclar Vivadent) (n=240 per material). Zirconia bars were sandblasted (35 ?m Al2O3, 1.5 bar pressure). Lithium disilicate bars were HF etched (20 s, IPS Ceramic Etching Gel, Ivoclar Vivadent) and silanized with ESPE Sil (3M ESPE). Forty bars of zirconia were luted in twos perpendicular to each other as were 40 bars of lithium disilicate using RelyX Unicem Automix 2 (3M ESPE), G-Cem LinkAce (GC Europe) or Maxcem Elite (Kerr) in self- or dual-curing mode. Half of the specimens from each material were submitted to tensile bond strength (TBS) testing after 24-h storage in distilled water at 37°C, and half underwent TBS testing after thermocycling (5000 cycles, 5°C/55°C, 30-s dwell time). Bond strength values for each bonding substrate were analyzed using one-way ANOVA (Student-Newman- Keuls, ?=0.05).On zirconia, dual-curing resulted in significantly (p<0.05) higher tensile bond strengths compared to self-curing, with the exception of RelyX Unicem 2 after thermocycling. Thermocycling significantly (p<0.05) reduced the tensile bond strength of Maxcem Elite to zirconia in both curing modes. The TBS of self-adhesive cements to lithium disilicate showed no significant (p>0.05) difference between the different curing modes and after thermocycling.For most of the investigated self-adhesive cements, bond strengths to zirconia were increased by dual curing; this was not true for lithium disilicate. For luting on zirconia with self-adhesive cements, dual curing is strongly recommended in clinical situations.
EVALuna2:24671